THE IMPLEMENTATION OF DISCUSSION MEETING TECHNIQUE TO IMPROVE STUDENTS’ SPEAKING ABILITY AT SECOND GRADE OF SMAN 1 BANGKUNAT-BELIMBING IN 2016/2017 - Ida Lisma; Harpain Harpain (LINGUISTIKA, 2017)
The objective of this research were to know how discussion meeting technique can give an effect to students’ motivation, and confidence in the class, and to see student improvement of speaking in experiencing discussion meeting technique. This technique used as an effort to help the students to improve their speaking ability. Discussion meeting technique made the students have motivation and more confidence to improve the students’ speaking ability. In this research, the researcher used the descriptive qualitative method. This kind of method was used to feel the experience the real world, and also to know people’s point of view of a certain phenomenon. It was also used to obtain the truthful, precise, and well-organized explanation about students’ speaking in experiencing discussion meeting of speaking class. The research was done at SMAN 1 Bangkunat Belimbing that consisted of twenty students. To gather the data, the researcher did the observation and distributed the questionnaire at the end of her observation. The data was analyzed by combining the result of observation and questionnaire in several paragraphs. The result of this research showed that when firstly the researcher implemented this technique, student felt confused of what they should do in the class, but finally they are able to follow the instruction from the researcher. So, the class in the end ran successfully. From the questionnaire result also showed mostly positive feedback in experiencing discussion meeting technique. So, the improvement of students’ speaking ability was better than before. The combination of those two instruments is that discussion meeting technique is able to facilitate them in speaking class. They mostly agreed this technique could make them have motivation and more confidence in this class and could help them in improving their skill; also it could awake them that they need to be more responsible of their own learning in the class.